2020
DOI: 10.1002/adfm.202007661
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus@Laser‐Engraved Graphene Heterostructure‐Based Temperature–Strain Hybridized Sensor for Electronic‐Skin Applications

Abstract: Smart electronic skin (e‐skin) requires the easy incorporation of multifunctional sensors capable of mimicking skin‐like perception in response to external stimuli. However, efficient and reliable measurement of multiple parameters in a single functional device is limited by the sensor layout and choice of functional materials. The outstanding electrical properties of black phosphorus and laser‐engraved graphene (BP@LEG) demonstrates a new paradigm for a highly sensitive dual‐modal temperature and strain senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 51 publications
1
128
0
Order By: Relevance
“…[33] Alternatively, multifunctional sensors that can transduce each stimulus into separate signals can overcome these limitations. [279] Very recently, Chhetry et al [279] reported a skin-attachable temperature-strain multifunctional sensor by a black phosphorus and laser-engraved graphene (BP@LEG) heterostructure into an ultrathin, highly stretchable polymer substrate, as shown in Figure 22a. This multifunctional sensor exhibits remarkable temperature-dependent characteristics and linear microcrack propagation behavior, which are suitable for the thermoresistive sensor (Figure 22b,c) and strain sensor (Figure 22d,e), respectively.…”
Section: E-skin Systems With Multiple Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Alternatively, multifunctional sensors that can transduce each stimulus into separate signals can overcome these limitations. [279] Very recently, Chhetry et al [279] reported a skin-attachable temperature-strain multifunctional sensor by a black phosphorus and laser-engraved graphene (BP@LEG) heterostructure into an ultrathin, highly stretchable polymer substrate, as shown in Figure 22a. This multifunctional sensor exhibits remarkable temperature-dependent characteristics and linear microcrack propagation behavior, which are suitable for the thermoresistive sensor (Figure 22b,c) and strain sensor (Figure 22d,e), respectively.…”
Section: E-skin Systems With Multiple Sensorsmentioning
confidence: 99%
“…e) Time-dependent resistance response of the sensor for seven consecutive cycles of strains from 2% to 20%. Reproduced with permission [279]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%
“…First, the TS comprising a CNF550 film imparted a much larger variation in relative electrical resistance change (ΔR/R 0 ) for a given temperature rise than those made of CNF films prepared at higher CTs (Figure S3a, Supporting Information). The temperature coefficient of resistance (TCR) is a measure of the sensitivity of a resistive TS and is given by: [32,42] TCR / 100%…”
Section: Performance Of the All Resistive Cnf Multifunctional Sensor With Stimulus Discriminabilitymentioning
confidence: 99%
“…[20,22] Therefore, it is highly desired to develop sensitive multifunctional sensors having stimulus discriminability and yet benefiting from simple, cost-effective fabrication, and readout systems, for instance, a multifunctional sensor whose outputs are only given in electrical resistance signals. [30] However, such all resistive multifunctional sensors capable of stimulus discriminability have rarely been reported to date because conductive fillers, such as graphene, [31][32][33] carbon nanotubes, [34][35][36] and metal nanoparticles, [37][38][39] which are commonly used in the resistive PSs are known to exhibit significant sensitivity to temperature arising from their thermoresistive characteristics. [26,40] This paper is dedicated to developing flexible, all resistive multifunctional sensors which can simultaneously detect and discriminate temperature and pressure stimuli in real time, using carbon nanofiber (CNF) films as the sole sensing material.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature sensing ability of this Gr/SF/Ca 2+ ‐based temperature sensor was explored by attaching the sensor to a human hand. Chhetry et al [ 691 ] recently developed a resistive type temperature sensor based on BP and laser‐engraved graphene (BP@LEG). Park and colleagues addressed the ambient stability issue of BP by encapsulating the BP@LEG into an ultrathin flexible polystyrene‐block‐poly(ethylene‐ran‐butylene)‐block‐polystyrene (SEBS) substrate.…”
Section: D Materials‐based Wearable Sensors For Human Health Applicationsmentioning
confidence: 99%